Day case 'treat and transfer' ERCP service under general anaesthesia. Issue 4 (9th March 2018) - El-Sherif, Yasser; Hunt, John; Suddle, Abid; Prater, Brian; Reffitt, David; Devlin, John; Harrison, Phillip; Joshi, Deepak
Abstract : Objective: General anaesthesia (GA) has been increasingly used for advanced endoscopic procedures in particular endoscopic retrograde cholangiopancreatography (ERCP). Given the increasing pressure on many hospitals, the delivery of such service on a regular basis may not always be possible. We established a new day case 'GA ERCP' service. We describe our experience in evaluating the safety and overall feasibility of this new service. Design: Prospective database has been interrogated for the period from March 2015 to December 2016. We documented patients' demographics, ERCP indications, American Society of Anesthesiologists (ASA) status, Cotton grade and complications. Results: 67 patients were referred to endoscopy unit at King's College Hospital (KCH), for urgent day case GA ERCP from nine referring hospitals. The main indications were failed ERCP under sedation 47.8% (32/67), and unavailability of ERCP locally 41.8% (28/67). A total of 64 patients were actually transferred to KCH; 57.8% (37/64) women with a median age 55.8 years (range 23–90). 78.1% (50/64) of patients had a virgin papilla, with 39% (25/64) were ASA ≥3. The Cotton grade was ≥ 3 in 50% (32/64) patients. ERCP was completed successfully in 87.5% (56/64). For patients with previous failed ERCP, repeat ERCP under GA was successful in 75% (24/32). All patients were safely discharged back to their referring hospitals after the short observation period post-ERCP. Conclusions: Urgent inpatient transfers between hospitals for performing ERCP under GA as a day case is safe and feasible. The new GA ERCP pathway can be replicated by other UK centres.